Psychological well-being of ex-drug addicted counselee in post-rehabilitation education - Rudi Haryadi; Eka Sri Handayani; Sri Ayatina Hayati (Program Studi bimbingan Konseling PPs UNM Makassar, 2020)
This study aims to analyze the level of psychological well-being of ex-drug addicted counselee in post-rehabilitation education. The study was conducted in 2 communities of post-rehabilitation education providers in Semarang city. The level of psychological well-being of 40 respondents was measured by filling in the 18-item psychological well-being scale developed by Ryff (r = 0.83; v = 0.97). Measurement includes indicators: (1) self-acceptance; (2) positive relationships with others; (3) autonomy; (4) environmental mastery; (5) purpose in life; and (6) personal growth. Hypothesis test results indicate that the level of psychological well-being of ex-drug addicted counselee in post-rehabilitation education is significantly greater or equal to 80 (t = 49,140; sig = 0,000). Based on the results of this study, it is recommended to further researchers to further explore certain differences in the level of psychological well-being of the counselee by the factors of age, demographics, educational background, and length of abstinence. In addition, further studies with a larger number of samples and questionnaire items are needed so that study results can be generalized to a wider population.Ardiantina, D. (2016). Studi Kasus Kehidupan Remaja Mantan Pecandu Narkoba. Jurnal Bimbingan dan Konseling, 5(1), 1-12.Astuti, R., & Ismandari, F. (2014). Gambaran Umum Penyalahgunaan Narkoba di Indonesia. Buletin Jendela Data dan Informasi Kesehatan. I, pp. 1-52. Jakarta: Kementrian Kesehatan RI.Aztri, S., & Milla, M. N. (2013). Rasa Berharga Dan Pelajaran Hidup Mencegah Kekambuhan Kembali Pada Pecandu Narkoba Studi Kualitatif Fenomenologis. Jurnal Psikologi, 9(1), 48-63.Bhandari, S., Dahal, M., & Neupane, G. (2015). Factors Associated With Drug Abuse Relapse: A Study On The Clients Of Rehabilitation Centers. Al-Ameen Journal of Medicine and Science, 8(4), 293-298.BNN. (2015). Laporan Akhir Survei Nasional Perkembangan Penyalahgunaan Narkoba Tahun Anggaran 2014. Jakarta: Badan Narkotika Nasional Indonesia.Buchanan, T. (2011). Attention Defi cit/Hyperactivity Disorder and Well-being: Is Social Impairment an Issue for College Students with ADHD? Journal of Postsecondary Education and Disability, 24(3), 193-210.Bukoye, R. O. (2017). Academic Stress and Drug Abuse as Factors Inhibiting Psychological Well-Being Among Undergraduates: It’s Counselling Implications. European Scientific Journal, 13(8), 60-74.Chong, J., & Lopez, D. (2008). Predictors of Relapse for American Indian Women After Substance Abuse Treatment. Journal of The National Center, 14(3), 24-47.Dogaheh, E. R., Jafari, F., Sadeghpour, A., Mirzaei, S., Maddahi, M. E., Hosseinkhanzadeh, A. A., & Arya, A. R. (2013). Psychological Well-Being and Quality of Sleep in Addicts under Methadone Maintenance Treatment. Research Papers, 1(2), 71-75.Fard, A. E., Rajabi, H., Delgoshad, A., Rad, S. A., & Akbari, S. (2014). The Possible Relationship between University Students' Personality Traits, Psychological Well-being and Addiction Potential. International Journal of Social Science Studies, 2(2), 120-125.Garcia, D., Nima, A. A., & Kjell, O. N. (2014). The Affective Profiles, Psychological Well-Being, and Harmony: Environmental Mastery and Self-Acceptance Predict the Sense of a Harmonious Life. PeerJ, 1-21.Green, M., & Elliott, M. (2010). Religion, Health, and Psychological Well-Being. Journal of Religion and Health, 49, 149-163.Greenfield, E., Vaillant, G., & Marks, N. (2009). Doformal religious participation and spiritual perceptions have independent linkages with diverse dimensions of psychological well-being? Journal of Health and Social Behavior, 50, 196–212.Haryadi, R. (2018). Prospek Konseling Komunitas bagi Individu Eks-Pecandu Narkoba (Studi Pada Lembaga Pasca-Rehabilitasi Narkoba Di Kota Semarang). Konseli (Jurnal Bimbingan dan Konseling), 5(1), 73 - 84.Ibrahim, F., & Kumar, N. (2009). Factors Effecting Drug Relapse in Malaysia: An Empirical Evidence. Asian Social Science, 5(12), 37-44.Lindfors, P., Berntsson, L., & Lundberg, U. (2007). Total workload as related to psychological well-being and symptoms in full-time employed female and male white-collar workers. International Journal of Behavior and Medicine, 13, 131-137.Martin, R. A., MacKinnon, S., Johnson, J., & Rohsenow, D. J. (2011). Purpose in life predicts treatment outcome among adult cocaine abusers in treatment. Journal of Substance Abuse Treatment, 40, 183–188.Ryff, C. D. (2014). Psychological Well-Being Revisited: Advanced in the Science and Practice of Eudaimonia. Psychoterapy and Psychosmoatics, 83, 10-28.Ryff, C. D., Love, G. D., Miyamoto, Y., Markus, H. R., Curhan, K. B., Kitayama, S., . . . Karasawa, M. (2014). Culture and the promotion of well-being in East and West: Understanding varieties of attunement to the surrounding context. In G. A. Fava, & C. Ruini, Increasing psychological well-being in clinical and education settings: Interventions and cultural contexts (Vol. 8th, pp. 1-19). New York: Springer.Schaefer, S. M., Boylan, J. M., Reekum, C. M., Lapate, R. C., Norris, C. J., Ryff, C. D., & Davidson, R. J. (2013). Purpose in Life Predicts Better Emotional Recovery for Negative Stimuli. Plos ONE, 8(11), 1-9.Schwartz, R. P., Kelly, S. M., O’Grady, K. E., Mitchell, S. G., Peterson, J. A., Reisinger, H. S., . . . Brown, B. S. (2008). Attitudes toward buprenorphine and methadone among opioid-dependent individuals. American Journal of Addicton, 17, 396–401.Seligman, M. E. (2010). Flourish: Positive Psychology and Positive Intervention. Michigan: University of Michigan.Sharma, A. K., Upadhyaya, S. K., Bansal, P., Nijhawan, M., & Sharma, D. (2012). A Study of Factors Affecting Relapse in Substance Abuse. Indian Journal of Science and Technology, 2(1), 31-35.Siddiqui, S. (2015). Impact of self-efficacy on psychological well-being among undergraduate students. The International Journal of Indian Psychology, 2(3), 5-17.Strauser, D., Lustig, D., & Çıftçı, A. (2008). Psychological well-being: its relation to work personality, vocational identity, and career thoughts. Journal of Psychology, 142, 21–35.Vasquez, C., & Castilla, C. (2007). Emociones Positivas y Crecimiento Postraumatico en el Cancer de Mama. Psicooncologia, 4, 385-404.